Termination of Construction Contracts Under the UAE Law and FIDIC - KADRI, SARAH (2023)
Construction is among the industries, if not the top industry, that play the most key role in the economy of the United Arab Emirates (UAE). Like all other industries, Construction faced recently exceptional critical challenges due to the pandemic which caused an extensive inability, or at least a substantial hardship, for innumerable parties to comply with their contractual obligations. Eventually, this resulted in an increase in the number of delays in the projects’ deliveries and, in numerous cases, resulted in the dissolution of the contracts. Consequently, the importance of the concept of contracts termination gained considerable attention compared to the pre-pandemic era, as the relevant clauses and legal provisions were the lifeline equipment to some parties, while they were the calamity to many others. For this purpose, this paper focuses on the law provisions related to the termination of contracts under UAE Civil Code, and their application by the UAE courts. The paper also reviews the relevant provisions in Fidic Red Book (1987, 1999 and 2017) and highlights their applicability under UAE law. The paper concludes that a contract can be lawfully terminated under both the UAE law and FIDIC Red Book (1987, 1999 and 2017) under specific conditions and subject to certain requirements. Therefore, it is essential for the parties to be cautious and to be fully aware of the law, the contractual rights, obligations, and procedures, while drafting the contract and prior to taking such a termination decision and declaring it officially to the other party. This dissertation provides a comprehensive overview of the concept of the termination of contracts under the UAE law and under FIDIC (Red Book).